2008
DOI: 10.1111/j.1471-4159.2008.05217.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in G2019S‐LRRK2‐associated neurite shortening in differentiated SH‐SY5Y cells

Abstract: Neuritic retraction represents a prominent feature of the degenerative phenotype associated with mutations in leucine rich repeat kinase 2 (LRRK2) that are implicated in autosomal dominant and some cases of sporadic Parkinson’s disease. Alterations in macroautophagy, the vacuolar catabolism of cytoplasmic constituents, have been described in Parkinson’s disease. In this study, we utilized retinoic‐acid differentiated SH‐SY5Y cells to determine whether autophagy contributes to mutant LRRK2‐associated neurite de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
450
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(493 citation statements)
references
References 49 publications
41
450
1
1
Order By: Relevance
“…These studies also suggest that neurite pathology precedes dopaminergic neuronal death by apoptosis (14,15). Although autophagy and increased Tau inclusions have been described in conjunction with neurite shortening, the only signaling pathway linked to the G2019S LRRK2-induced neurite pathology is the ERK pathway (10,15,(17)(18)(19)(20).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also suggest that neurite pathology precedes dopaminergic neuronal death by apoptosis (14,15). Although autophagy and increased Tau inclusions have been described in conjunction with neurite shortening, the only signaling pathway linked to the G2019S LRRK2-induced neurite pathology is the ERK pathway (10,15,(17)(18)(19)(20).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
“…Activated Rac and Cdc42 also signal through PAK to activate LIM kinase, which inhibits downstream cofilin, thereby blocking actin depolymerization (30). Plowey et al (15) found that an ERK inhibitor abolished the G2019S LRRK2-induced neurite retraction in their SH-SY5Y cellular model. PAK signaling through ERK is an interesting upstream trigger that might implicate Rho GTPases in the pathogenesis of neurite shortening.…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%
“…Consequently, the irreversible binding of mutant a-synuclein to the lysosome blocks the binding of other substrates, resulting in a general impairment of the CMA pathway and further a-synuclein accumulation 110 . Proteins related to familiar PD, such as DJ-1 or LRRK2, significantly alter autophagy 111,112 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…In contrast, overexpression of both wild-type LRRK2 and LRRK2 G2019S , but not catalytically inactive forms of the protein, induces an AMPK-mediated upregulation of autophagy (36). Other studies have reported autophagy upregulation following overexpression of LRRK2 G2019S by an ERK1/2-mediated mechanism (37,38).…”
Section: Autophagy In the Pathogenesis Of Neurodegenerative Diseasementioning
confidence: 86%